Base-case model for measurement uncertainty in a reverberation chamber including frequency stirring - Gifuni, Angelo; Bastianelli, Luca; Moglie, Franco; Mariani Primiani, Valter; Gradoni, Gabriele (Institute of Electrical and Electronics Engineers, 2017)
We address the uncertainty of reverberation chamber (RC) measurements in presence of both mechanical and frequency stirring (FS). A base-case model is derived for reverberation fields affected by the measurement uncertainty due to the lack of a perfect statistical uniformity of fields in a RC. It is found that the measurement uncertainty associated with the FS depends on both the total uncorrelated samples and the local insertion loss (IL). The local IL depends on the frequency stirring bandwidth (FSB). The model allows us for obtaining separate measurement uncertainty contributions. Measurements support the achieved uncertainty model. In particular, results show that the dependence on the IL is normally rather weak also when very wide FSBs are used.